UTILITY OF COMPUTED TOMOGRAPHY FOR THE ASSESSMENT OF TISSUE REGENERATE DENSITY AFTER CHONDROPLASTY IN AN EXPERIMENT WITH RABBITS - G. P. Kotelnikov; D. A. Dolgushkin; V. A. Lazarev; P. M. Zel'ter (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The problem of repair of full-layer defects in the articular surface remains highly relevant. New methods of  chondroplasty should be tested in preclinical studies on animals. Full quality control of the newly formed regenerate is often possible only when an animal is euthanized. However, the design of some experiments implies animal observation for a long time. Therefore, lifetime assessment of the quality of the formed tissue  regenerate after chondroplasty would be very convenient. We have developed a new method for assessing the  quality of regenerate using computed tomography in preclinical studies on rabbits. This method can be used to measure completeness of defect filling, density of the newly formed regenerate, and also to evaluate similar  parameters of the newly formed tissue in the area of the subchondral bone, intermediate zone, and cartilage. The  new method makes it possible to assess the dynamics of formation and restructuring of newly formed tissue afterchondroplasty without euthanizing the animal.